2020
DOI: 10.1111/jch.14061
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of changes in the levels of catecholamines and blood pressure with continuous positive airway pressure therapy in obstructive sleep apnea

Abstract: Obstructive sleep apnea (OSA) is a common condition among overweight and obese individuals. 1 About half of patients with OSA have hypertension, and about half of patients with hypertension have OSA. 2 Causal link between OSA and hypertension is complex and remains debatable, but hypertension may in part arise from increased sympathetic nerve activity induced by hypoxic stress. 3 OAS is associated with a number of secondary health complications, most notably cardiovascular disease, 4 and co-existing cardiometa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 59 publications
2
7
0
Order By: Relevance
“…Excluding the study using salivary cortisol from the rest of the forest plot in PCS, or splitting the six RCT into plasma and salivary cortisol studies showed and blood pressure was also reduced by CPAP treatment. 50,51 The reduction of 5.4 mmHg of SBP and 3.3 mmHg DBP by CPAP in the present study was remarkably similar to the results observed in our previous meta-analysis of CPAP and catecholamines. 50 These together suggest that CPAP reduces stress induced by OSA.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Excluding the study using salivary cortisol from the rest of the forest plot in PCS, or splitting the six RCT into plasma and salivary cortisol studies showed and blood pressure was also reduced by CPAP treatment. 50,51 The reduction of 5.4 mmHg of SBP and 3.3 mmHg DBP by CPAP in the present study was remarkably similar to the results observed in our previous meta-analysis of CPAP and catecholamines. 50 These together suggest that CPAP reduces stress induced by OSA.…”
Section: Discussionsupporting
confidence: 91%
“…50,51 The reduction of 5.4 mmHg of SBP and 3.3 mmHg DBP by CPAP in the present study was remarkably similar to the results observed in our previous meta-analysis of CPAP and catecholamines. 50 These together suggest that CPAP reduces stress induced by OSA. In response, secretion of stress hormones such as cortisol and catecholamines are also decreased.…”
Section: Discussionsupporting
confidence: 91%
“…Several meta‐analyses showing a beneficial effect of CPAP therapy on BP reduction have been reported. 7 , 21 , 22 However, in those studies, the evaluation of BP was performed by office BP and/or ambulatory BP monitoring. Evidence of an association between morning home BP and the progression of target organ damage or cardiovascular events has been accumulating.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with those observed in clinical studies of the effects of CPAP treatment on catecholamines and blood pressure in patients with OSA, but the reduction in blood pressure is greater in this study (31 mmHg) compared with that in clinical studies (<10 mmHg). 27 , 28 There are a number factors that may contribute to this difference. In this study, phaeochromocytoma was excluded in all patients, therefore a good response to CPAP treatment would be expected.…”
Section: Discussionmentioning
confidence: 99%